2009
DOI: 10.1126/science.1177127
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Transmission of Swine-Origin 2009 A(H1N1) Influenza Virus in Ferrets

Abstract: The swine-origin A(H1N1) influenza virus that has emerged in humans in early 2009 has raised concerns about pandemic developments. In a ferret pathogenesis and transmission model, the 2009 A(H1N1) influenza virus was found to be more pathogenic than a seasonal A(H1N1) virus, with more extensive virus replication occurring in the respiratory tract. Replication of seasonal A(H1N1) virus was confined to the nasal cavity of ferrets, but the 2009 A(H1N1) influenza virus also replicated in the trachea, bronchi, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
528
5
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 551 publications
(590 citation statements)
references
References 17 publications
54
528
5
3
Order By: Relevance
“…Both type I and type II pneumocytes were infected. Ferrets inoculated with pandemic H1N1/09 virus displayed more severe symptoms, involving the entire respiratory tract, compared with ferrets inoculated with seasonal influenza A (H1N1) which displayed symptoms of necrotising rhinitis only (17). The detection of pandemic H1N1/09 virus in the intestinal tract of some infected ferrets is consistent with the gastrointestinal complaints from several human patients with pandemic H1N1/09 infection (16).…”
Section: Pathogenesissupporting
confidence: 60%
See 2 more Smart Citations
“…Both type I and type II pneumocytes were infected. Ferrets inoculated with pandemic H1N1/09 virus displayed more severe symptoms, involving the entire respiratory tract, compared with ferrets inoculated with seasonal influenza A (H1N1) which displayed symptoms of necrotising rhinitis only (17). The detection of pandemic H1N1/09 virus in the intestinal tract of some infected ferrets is consistent with the gastrointestinal complaints from several human patients with pandemic H1N1/09 infection (16).…”
Section: Pathogenesissupporting
confidence: 60%
“…Pandemic H1N1/09 virus pathogenicity and transmissibility studies conducted in ferrets, mice and cynomolgus macaques proved that the pandemic strain is more pathogenic than seasonal H1N1 influenza, as the virus replicated more efficiently in the lungs of all three animal models (15)(16)(17). Macaque lungs demonstrated severe thickening of the alveolar walls, and the alveolar spaces were filled with inflammatory infiltrates and oedematous exudates.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial number of previously healthy patients have been reported to complain of dyspnea sensations or to have pneumonia (2, 3). The novel influenza A (H1N1) virus has an affinity to airway epithelial cells, thus it could cause bronchitis and bronchiolitis (12,13). Pulmonary emphysema in smokers includes such a large portion in the general population that this alone could not account for the frequency of the non-obvious risk population among those who require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the 2009 H1N1 influenza strain, the World Health Organization (WHO) has recommended that patients receive 5 days of treatment with antiviral agents 4. However, animal models show that the 2009 H1N1 virus replicates more efficiently than seasonal influenza viruses in the respiratory tract 5, 6, 7. In addition, several studies have shown that the 2009 H1N1 virus can still be present for 8 days or more 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%